2022
DOI: 10.3390/foods11040575
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Killed Enterococcus faecalis EF-2001 Attenuate Lipid Accumulation in Diet-Induced Obese (DIO) Mice by Activating AMPK Signaling in Liver

Abstract: To explore the inhibitory mechanism of heat-killed Enterococcus faecalis, EF-2001 on hepatic lipid deposition, a diet-induced obese (DIO) animal model was established by high-fat diet (HFD). The DIO C57BL/6 mice were divided into four groups: the normal group without HFD (ND, n = 8), obesity group (HFD, n = 8), experimental group (HFD + EF-2001, 200 mg/kg, n = 8), and positive control group (HFD + Orlistat, 60 mg/kg, n = 8). After 4 weeks, liver and adipose tissue were fixed in 10% paraformaldehyde, followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Recently, another notable study has reported the influence of weight control based on the impact of EF-2001 administration on the AMPK pathway in mice with obesity induced by HFD. Fan et al reported that EF-2001 remarkably elevated the expressions of p-AMPK and p-ACC in mice and suggested that EF-2001 decreases hepatic lipid accumulation in the DIO model mice via AMPK pathway while improving livers injured by an HFD [ 23 ]. AMPK is an important factor in regulating homeostasis and basal metabolism in mammalian cells [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, another notable study has reported the influence of weight control based on the impact of EF-2001 administration on the AMPK pathway in mice with obesity induced by HFD. Fan et al reported that EF-2001 remarkably elevated the expressions of p-AMPK and p-ACC in mice and suggested that EF-2001 decreases hepatic lipid accumulation in the DIO model mice via AMPK pathway while improving livers injured by an HFD [ 23 ]. AMPK is an important factor in regulating homeostasis and basal metabolism in mammalian cells [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Converting this dose to an adult weight of 60 kg, the clinical dosage for adults is 25 mg/kg/day. The equivalent dose for mice is 12.3 times that of human adults, 307.5 mg/kg/day probiotics [ 23 ]. Additionally, according to previous reports on EF-2001, various oral concentrations of EF-2001 were administered in our mouse experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Enterococcus faecalis (E. faecalis), one of the most abundant species of the Enterococcus genus in fecal content, has been frequently applied as a probiotic in food and dietary supplements. 20 And E. faecalis is beneficial and assists in the treatment of various disorders, 21,22 which attenuates lipid accumulation and possesses radioprotection and anti-inflammation. 21 However, the role of E. faecalis in HUA remains unclear.…”
mentioning
confidence: 99%